Belgium : Financial System Stability Assessment-Technical Note- Stress Testing the Banking and Insurance Sectors and Systemic Risk Analysis. (IMF Staff Country Reports; Country Report ;, 2018)
This Technical Note discusses the results of the stress testing of Belgium's banking and insurance sectors. Belgium's financial sector remains resilient in the face of the rising cyclical vulnerabilities, but there is a need for closely monitoring risks. Stress tests on banks and insurance companies confirm that they can absorb credit, sovereign, and market losses in the event of a severe deterioration in macro-financial conditions. All banks meet minimum capital requirements and none needs to draw down its capital conservation buffer over the stress horizon. The risk of interbank contagion through direct exposures is low. Insurance companies are also generally resilient and losses incurred in the stress scenarios by those that belong to banking groups do not threaten the soundness of those groups.